Economic upgrading in global value chains: concepts and measures - Marcato, Marília Bassetti (2020)
This paper has critically documented a vast literature addressing the multi-layered outcomes associated with participating in global value chains (GVCs). In particular, this paper reviews and synthesizes the definitions and quantitative measures of one particular dimension of the GVC analysis that is two-fold: the economic and social upgrading. More specifically, we discuss the economic perspective of upgrading, which is usually associated with “moving into higher value-added stages”, and it is commonly assumed to be followed by positive spillovers regarding technology and productivity. This paper emphasizes the important diversity of definitions and measures within the GVC literature, considering it as a reflection, to a certain extent, of the absence of a systematic theoretical apparatus in the GVC literature. The paper concludes with some considerations on the role of policymakers in promoting social upgrading as an important topic in the GVC research agenda.